2019
DOI: 10.1007/s12039-019-1616-7
|View full text |Cite
|
Sign up to set email alerts
|

Beryllium ion sensing through the ion pair formation between the electrochemically reduced ferrocenyl naphthoquinone radicals and $$\hbox {Be}^{2+}$$ ions

Abstract: We explored the mechanistic aspects of ion pair formation between electrochemically reduced radicals (Fc-cnq-1a • − /Fc-cnq-1b • −) and dianions (Fc-cnq-1a 2− /Fc-cnq-1b 2−) of ferrocenyl naphthoquinones (Fc-cnq-1a and Fc-cnq-1b) and several metal ions by cyclic voltammetry (CV), square wave voltammetry (SWV) and spectroelectrochemistry, for the first time. The experiments demonstrated that Fc-cnq-1a 2− /Fc-cnq-1b 2− were moderately affected with Na + , K + and Cs + by slightly shifting to the anodic side, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…4c) gives a straight line with a slope value of 56.9 mV (R 2 = 0.9868) which shows that formation ion-pair complex between NR-phosphate and nuclear aggregates of polyamines (NAPs) has linear relationship and such correlation has been reported. 56,57 Electrochemical impedance spectroscopy (EIS) studies confirm the formation of ion-pair complexation; this can be observed from the change in R ct values upon addition of cadaverine. A large increase in charge resistance (73.98kΩ) was observed and this can be attributed to the interaction of PNR/GCE with cadaverine through phosphate ion bridging (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…4c) gives a straight line with a slope value of 56.9 mV (R 2 = 0.9868) which shows that formation ion-pair complex between NR-phosphate and nuclear aggregates of polyamines (NAPs) has linear relationship and such correlation has been reported. 56,57 Electrochemical impedance spectroscopy (EIS) studies confirm the formation of ion-pair complexation; this can be observed from the change in R ct values upon addition of cadaverine. A large increase in charge resistance (73.98kΩ) was observed and this can be attributed to the interaction of PNR/GCE with cadaverine through phosphate ion bridging (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…[34][35][36] Electrochemical sensors based on ion-pair z E-mail: giribabuk@cecri.res.in formation have been previously reported. 37,38 Herein, we study an electrochemical non-enzymatic sensing methodology for the detection of cadaverine and putrescine via aggregation of amine with poly (neutral red) (PNR) on GCE under phosphate buffer medium. To validate their detection capability real fish specimen with artificially spiked biogenic amines were tested and observed results suggest that the ion-pair formation based biomarker detection may find intrinsic role in non-enzymatic sensor application.…”
mentioning
confidence: 99%
“…In this study, a 1,4-naphthoquinone compound functionalized with 8-aminoquinoline was used as a sensor platform to provide the quite selective and ultrasensitive quantification of Cu 2+ ions. NQ structures play a significant role in the sensing of metal cations , due to their photochemical and photophysical durabilities, which improves the probe life and suitability of the ICT process . These molecules can be easily functionalized especially from their α position via amine derivatives .…”
Section: Resultsmentioning
confidence: 99%
“…Various characterization techniques confirmed the formation of a complex between compound 74 and Al 3+ , and were successfully used to find out the Al 3+ content in environmental samples (Figure 7). Finally, the method employed by Atasen explained the sensing potential of Be 2+ by ion pair formation with ferrocenyl naphthoquinones radicals and dianions [75]. Cyclovoltammetric analysis revealed that the sensitivity effect was more pronounced in the case of Be 2+ among all alkaline earth metals that formed an ion pair with Fc-cnq-Ia and could selectively sense the ultra-trace amount of Be 2+ (LOD 3.6 ppb).…”
Section: Chemosensing Applicationsmentioning
confidence: 99%